129 The CHR9P21 risk locus affects IL-1/TLR signalling in VSMC. (June 2018) - Basatemur, Gemma; Ackers-Johnson, Matthew; Schoonejans, Josca; Kazachenka, Anastasiya; Lam, Brian; Ma, Marcella; Brimpari, Minodora; Patel, Meghana; Saleh, Nada; Murphy, Deirdre; Zhao, Tian; Yeo, Giles; et al.
Abstract : The genetic associations linking the chromosome 9 p21 (chr9p21) locus with cardiovascular diseases, such as aneurysm and coronary artery disease, are well characterised. However, the underlying molecular mechanism remains unclear. The chr9p21 locus is also associated with traits such as arterial stiffness, implicating a role in vascular cell biology. We investigated whether the risk variants affect vascular smooth muscle cell (VSMC) responses to inflammation. Methods: We used recently developed and well characterised methods to differentiate VSMC from induced pluripotent stem cells (iPS) and compared the responses of risk and non-risk genotype iPS-VSMC to a range of IL-1 and TLR agonists. Results: Risk and non-risk genotype iPS differentiated equally well to iPS-VSMC. However, the chr9p21 risk genotype conferred increased sensitivity to stimulation with IL-1alpha, IL-1beta and selective TLR agonists, due to increased expression of interleukin-1 receptor-associated kinase 4 (IRAK4). IRAK4-independent inflammatory responses remained unaffected by the risk genotype. IRAK4 expression was increased in risk iPS-VSMC as a consequence of altered epigenetic remodelling, including DNA methylation, of the IRAK4 promoter. Conclusions: Our study establishes a mechanistic link between the chr9p21 locus, inflammation and susceptibility to cardiovascular diseases, and provides support for the targeted use of therapies that inhibit IRAK4-dependent pathways, such as IL-1 signalling, in individuals of chr9p21 risk genotype.